2019
DOI: 10.12669/pjms.35.1.211
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent injection of Methylprednisolone Sodium Succinate in the treatment of Cervical Spinal Cord injury complicated with incomplete paraplegia

Abstract: Objective: To evaluate the clinical efficacy and safety of intermittent injection of methylprednisolone sodium succinate in the treatment of cervical spinal cord injury complicated with incomplete paraplegia. Methods: Seventy-eight patients with cervical spinal cord injury complicated with incomplete paraplegia who were admitted between August 2016 and December 2017 were enrolled and grouped into an observation group and a control group using random number table, 39 in each group. Patients in the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…A total of 12 studies met the inclusion criteria and were incorporated into the meta-analysis. These included five randomized controlled trials (RCTs) [4,8,16,17,18] and seven observational studies (OBSs) [19,20,21,22,23,24,25]. The characteristics of the twelve studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 12 studies met the inclusion criteria and were incorporated into the meta-analysis. These included five randomized controlled trials (RCTs) [4,8,16,17,18] and seven observational studies (OBSs) [19,20,21,22,23,24,25]. The characteristics of the twelve studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were conducted in Asia, North America, and Europe. Assessment of the quality of the randomized trials using the risk of bias assessment tool yielded three studies with low bias [4,16,18] and two studies with high bias (Table 1) [8,17]. A total of four studies (2 RCTs and 2 OBSs) had short term follow-up [8,17,19,24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathophysiologic mechanism of SCI is complicated and includes the loss of neurons and glial cells, degeneration of extracellular matrix architecture and destruction of the neural circuit at the lesion site (Kumar et al, 2015; Chen et al, 2018a). Current strategies to cure SCI include surgical decompression (Jug et al, 2015; Liu et al, 2016) and pharmacotherapy (Wang et al, 2019) as well as focus on the restoration of nerve function by enhancing the survival of neurons after injury and promotion of axon regeneration via the injury site. Notably, surgical decompression and methylprednisolone could only remove the initial pathogen and preclude secondary damage of SCI.…”
Section: Introductionmentioning
confidence: 99%